1985
DOI: 10.1002/bbpc.19850890110
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Strontium by Graphitic Materials

Abstract: The sorption of Sr by graphitic materials used in high‐temperature gas‐cooled reactors was studied by applying high‐temperature mass spectro‐metry with a Knudsen cell and the isopiestic method. Sorption isotherms were determined for matrix graphite with Sr concentrations between 3.88 · 10−5 and 8.85 · 10−2 mol kg−1. The sorption enthalpies and partial pressures determined for concentrations greater than 1.5 · 10−4 mol kg−1 showed many properties of Freundlich isotherms. The evaluated vaporization enthalpies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The study reported in Ref. [8] also confirmed the pronounced dependence of sorptivity on a specific graphite structure. The authors measured Sr concentration in the A3--3 graphite and found that Sr inventory was bound primarily at the coked resin binder, which is a highly porous, nongraphitized material.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The study reported in Ref. [8] also confirmed the pronounced dependence of sorptivity on a specific graphite structure. The authors measured Sr concentration in the A3--3 graphite and found that Sr inventory was bound primarily at the coked resin binder, which is a highly porous, nongraphitized material.…”
Section: Introductionsupporting
confidence: 62%
“…For instance sorption isotherms for metallic fission products have been determined experimentally for the A3--3 graphite [7,8]. It was shown that while Sr and Cs bind strongly to the graphite, Ag is sorbed only in small quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The extremely low background ion intensities achievable allow measurement of partial pressures ≤10 -7 Pa [225], and even 10 -8 Pa in Knudsen cells [226].…”
mentioning
confidence: 99%
“…A series of fission product loadings are examined using KEMS to derive partial pressures of vapor species as a function of temperature. The loading‐dependent Sr enthalpy of vaporization, 317 as shown in Figure 22, indicates Sr is strongly chemisorbed on graphite. The loading dependence of partial pressures of the vapor species can be used to derive a sorption isotherm.…”
Section: Novel Applications Of Kemsmentioning
confidence: 99%
“…Several recent publications on desorption isotherms have been obtained using a KEMS system. Hilpert et al have studied the sorption of Sr and Cs on graphitic materials 317,318 using KEMS. Seelig et al 129 and Walton et al 319 have used KEMS to study sorption of Ag on graphitic materials.…”
Section: Novel Applications Of Kemsmentioning
confidence: 99%